The effects of traditional Thai massage delivered by parents on stereotypical behaviors in children with autism: a pilot study - Aonsri, Chanada; Tatchananusorn, Nutthanun; Auvichayapat, Paradee; Eungpinichpong, Wichai (Asia-Pacific Journal of Science and Technology, 2024)
Stereotypical behavior is one of the learning and social skills development problems that affect children with autism. Previous studies found that traditional Thai massage (TTM) could reduce stereotypical behaviors in autistic children. However, the effects of TTM delivered by the parents of autistic children have not been explored. This pilot study investigated the effects of TTM by parents on stereotypical behaviors in children with autism. A one-group pretest-posttest design was applied for 15 children, aged 4-16 years, with their parents' permissions. They participated in the study at the Special Education program of the Special Education Center of Khon Kaen University, Thailand. After being trained in a specialized TTM for children, the parents delivered 50-min TTM to children once a day, twice a week for eight weeks. The severity of autism and autistic behaviors were measured using Childhood Autism Rating Scale (CARS), and Autism Treatment Evaluation Checklist (ATEC), respectively. The functions of autonomic nervous systems were measured using Heart Rate Variability (HRV) to indicated physical and mental disorders such as stress. The data at baseline and the 8th week were analyzed using either an independent t-test or Wilcoxon signed-rank test. The study found that 16 sessions of TTM significantly improved measured data for autism in all children including the CARS (p<0.001), ATEC, speech/language/communication (p<0.001), sociability (p<0.001), sensory/cognitive awareness (p<0.001), health/physical/behavior (p< 0.001), and HRV (p<0.001). The results indicated that TTM performed by parents could be useful as an adjunct therapy for autistic children as it can reduce stereotypical behaviors and stress.